Tension and compression stress-strain asymmetry in passive skeletal muscle - Mohammadkhah, Melika (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2017)
The general aim of this study is to advance the knowledge of the relationship between the skeletal muscle passive compressive and tensile behaviour, and the microstructure of the muscle through combined experimental, microstructural and theoretical approaches. The mechanics of passive skeletal muscle are important in many biomechanical applications. Existing data from porcine tissue has shown a significant tension/compression asymmetry, which is not captured by current constitutive modelling approaches using a single set of material parameters, and an adequate explanation for this effect remains elusive. In this thesis, the passive elastic deformation properties of chicken pectoralis muscle are assessed for the first time, to provide deformation data on a skeletal muscle which is very different to porcine tissue. Uniaxial, quasi-static compression and tensile tests were performed on fresh chicken pectoralis muscle in the fibre and cross-fibre directions, and at 45° to the fibre direction. Results show that chicken muscle elastic behaviour is nonlinear and anisotropic. The tensile stress–stretch response is two orders of magnitude larger than in compression for all directions tested, which reflects the tension/compression asymmetry previously observed in porcine tissue. In compression the tissue is stiffest in the cross-fibre direction. However, tensile deformation applied at 45° gives the stiffest response, and this is different to previous findings relating to porcine tissue. Chicken muscle tissue is most compliant in the fibre direction for both tensile and compressive applied deformation. Generally, a small percentage of fluid exudation was observed in the compressive samples. Since collagen is the main structural protein in animal connective tissues, it is believed to be primarily responsible for their passive load-bearing properties. The direct detection and visualisation of collagen using fluorescently tagged CNA35 binding protein (fused to EGFP or tdTomato) is also reported for the first time on fixed skeletal muscle tissue. A working protocol is then established by examining tissue preparation, dilution factor, exposure time etc. for sensitivity and specificity. Penetration of the binding protein into intact mature skeletal muscle was found to be very limited, but detection works well on tissue sections with higher sensitivity on wax embedded sections compared to frozen sections. CNA35 fused to tdTomato has a higher sensitivity than CNA35 fused to EGFP but both show specific detection. Best results were obtained with 15 μm wax embedded sections, with blocking of non-specific binding in 1% BSA and antigen retrieval in Sodium Citrate. There was a play-off between dilution of the binding protein and time of incubation but both CNA35-tdTomato and CNA35-EGFP worked well with approximately 100 μg/ml of purified protein with overnight incubation, while CNA35- tdTomato could be utilized at 5 fold less concentration. The tension/compression asymmetry observed in the stress-strain response of skeletal muscle is not well understood. The optimised protocol is then applied to report qualitatively on skeletal muscle ECM reorganization during applied deformation using a combination of CNA35 binding protein and confocal imaging of tensile and compressive deformation of porcine and chicken muscle samples applied in both the fibre and cross-fibre directions. Results show the overall three-dimensional structure of collagen in perimysium visible in planes perpendicular (w1) and parallel (w2) to the muscle fibres in both porcine and chicken skeletal muscle. Furthermore, there is clear evidence of the reorganization of these structures under compression and tension applied in both the muscle fibre and cross-fibre directions, which generally explains anisotropy observed in the stress-strain response of skeletal muscle both in tension and compression for chicken and porcine tissues. These observations improve our understanding of how perimysium responds to three-dimensional deformations. The proposed three-dimensional illustration of perimysium structure is then used as a basis to create a microstructural-geometrical model to predict the passive mechanical stress-strain response observed in skeletal muscle. The current model represents the whole muscle response as a combination of both a group of muscle fibres (fascicle) response and the perimysium (ECM) response. It shows that although perimysium was believed to be a key element in the muscle stress response, the muscle fibres (in Tension-Fibre and Compression-XFibre deformations) also contribute to stress-stretch response since the order of magnitude for the stress in muscle fibres is similar to that of perimysium. The model shows more asymmetric response than previously published micromechanical model (Gindre et al., 2013). The model yields a good prediction of the whole muscle behaviour in Tension-Fibre and Compression-Fibre deformations using the optimum values for the model parameters obtained from the conducted sensitivity studies; connective tissue percentage of pc=1.75 , Elast modulus of Ec=300 MPa, and perimysium sheet waviness of w=1.25. However, the model overestimates the Compression-XFibre deformation and underestimates the Tension-XFibre deformations even by using the optimum parameters. The current model attempts to relate the mechanical stress-stretch response observed in muscle to the collagen reorganization in the muscle microstructure under load application, which further help develop better constitutive models for finite element modelling purposes. The general aim of this study is to advance the knowledge of the relationship between the skeletal muscle passive compressive and tensile behaviour, and the microstructure of the muscle through combined experimental, microstructural and theoretical approaches. The mechanics of passive skeletal muscle are important in many biomechanical applications. Existing data from porcine tissue has shown a significant tension/compression asymmetry, which is not captured by current constitutive modelling approaches using a single set of material parameters, and an adequate explanation for this effect remains elusive. In this thesis, the passive elastic deformation properties of chicken pectoralis muscle are assessed for the first time, to provide deformation data on a skeletal muscle which is very different to porcine tissue. Uniaxial, quasi-static compression and tensile tests were performed on fresh chicken pectoralis muscle in the fibre and cross-fibre directions, and at 45° to the fibre direction. Results show that chicken muscle elastic behaviour is nonlinear and anisotropic. The tensile stress–stretch response is two orders of magnitude larger than in compression for all directions tested, which reflects the tension/compression asymmetry previously observed in porcine tissue. In compression the tissue is stiffest in the cross-fibre direction. However, tensile deformation applied at 45° gives the stiffest response, and this is different to previous findings relating to porcine tissue. Chicken muscle tissue is most compliant in the fibre direction for both tensile and compressive applied deformation. Generally, a small percentage of fluid exudation was observed in the compressive samples. Since collagen is the main structural protein in animal connective tissues, it is believed to be primarily responsible for their passive load-bearing properties. The direct detection and visualisation of collagen using fluorescently tagged CNA35 binding protein (fused to EGFP or tdTomato) is also reported for the first time on fixed skeletal muscle tissue. A working protocol is then established by examining tissue preparation, dilution factor, exposure time etc. for sensitivity and specificity. Penetration of the binding protein into intact mature skeletal muscle was found to be very limited, but detection works well on tissue sections with higher sensitivity on wax embedded sections compared to frozen sections. CNA35 fused to tdTomato has a higher sensitivity than CNA35 fused to EGFP but both show specific detection. Best results were obtained with 15 μm wax embedded sections, with blocking of non-specific binding in 1% BSA and antigen retrieval in Sodium Citrate. There was a play-off between dilution of the binding protein and time of incubation but both CNA35-tdTomato and CNA35-EGFP worked well with approximately 100 μg/ml of purified protein with overnight incubation, while CNA35- tdTomato could be utilized at 5 fold less concentration. The tension/compression asymmetry observed in the stress-strain response of skeletal muscle is not well understood. The optimised protocol is then applied to report qualitatively on skeletal muscle ECM reorganization during applied deformation using a combination of CNA35 binding protein and confocal imaging of tensile and compressive deformation of porcine and chicken muscle samples applied in both the fibre and cross-fibre directions. Results show the overall three-dimensional structure of collagen in perimysium visible in planes perpendicular (w1) and parallel (w2) to the muscle fibres in both porcine and chicken skeletal muscle. Furthermore, there is clear evidence of the reorganization of these structures under compression and tension applied in both the muscle fibre and cross-fibre directions, which generally explains anisotropy observed in the stress-strain response of skeletal muscle both in tension and compression for chicken and porcine tissues. These observations improve our understanding of how perimysium responds to three-dimensional deformations. The proposed three-dimensional illustration of perimysium structure is then used as a basis to create a microstructural-geometrical model to predict the passive mechanical stress-strain response observed in skeletal muscle. The current model represents the whole muscle response as a combination of both a group of muscle fibres (fascicle) response and the perimysium (ECM) response. It shows that although perimysium was believed to be a key element in the muscle stress response, the muscle fibres (in Tension-Fibre and Compression-XFibre deformations) also contribute to stress-stretch response since the order of magnitude for the stress in muscle fibres is similar to that of perimysium. The model shows more asymmetric response than previously published micromechanical model (Gindre et al., 2013). The model yields a good prediction of the whole muscle behaviour in Tension-Fibre and Compression-Fibre deformations using the optimum values for the model parameters obtained from the conducted sensitivity studies; connective tissue percentage of pc=1.75 , Elast modulus of Ec=300 MPa, and perimysium sheet waviness of w=1.25. However, the model overestimates the Compression-XFibre deformation and underestimates the Tension-XFibre deformations even by using the optimum parameters. The current model attempts to relate the mechanical stress-stretch response observed in muscle to the collagen reorganization in the muscle microstructure under load application, which further help develop better constitutive models for finite element modelling purposes.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin